The president as statesman : Woodrow Wilson and the Constitution - Stid, Daniel D. (American political thought., 2021)
A political scientist who went on to become president, Woodrow Wilson envisioned responsible government, in which a strong leader and principled party would integrate the separate executive and legislative powers - but this ideal was constantly challenged by political reality. Daniel Stid explores Wilson's evolving views on the notion of responsible government and his endeavors as a statesman to establish it in the United States. Stid graphically describes how Wilson grappled, with the constitutional separation of powers, first as an academic and then as president, and he demonstrates the importance of Wilson's effort for American political thought and history.